R&D competition and patent values - Pu-yan Nie; Hong-xing Wen; Chan Wang (Journal of Innovation & Knowledge (JIK), 2023)
Research and development (R & D) competition is standard, and it heavily affects patent values. This study captures R&D competition's effects on patent values using game-theory approaches. Cost-reduction patent values increase with technology level and decrease with the competition. Technology spillover's impact on innovation depends on R & D's properties. This study elucidates cooperative R & D and the allocation mechanism, and also develops the theory of cooperative innovation.
Keywords: 650; Patent industrialization; Patent values; R & D competition